2012
DOI: 10.1111/j.1346-8138.2011.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐type prostaglandin D synthase as a marker for the proliferative potential of melanocyte‐lineage cells in the human skin

Abstract: Melanocytes in the human epidermis actively produce and secrete various substances, thereby contributing to the maintenance of the skin homeostasis. Lipocalin-type prostaglandin D synthase (L-PGDS) that catalyzes the formation of prostaglandin D(2) (PGD(2) ) may be one of such secreted molecules. Once secreted, L-PGDS functions as a transporter for lipophilic ligands, including all-trans retinoic acid (RA). L-PGDS, therefore, may possess pleiotropic functions in the skin through PGD(2) and RA. We aimed to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…The observation of the present study that HPGDS transcripts were limited to melanocytes lends further support to a potential role in melanogenesis. Moreover, just as MITF, it was expressed at an early stage of melanocyte maturation which is consistent with the proposition that it may be involved in regulatory feed-back with MITF (Shimanuki et al, 2012; Takeda et al, 2006). Additionally, in human cell lines, it had been shown that prostaglandins positively enhanced tyrosinase activity (Abdel-Malek et al, 1987).…”
Section: Discussionsupporting
confidence: 87%
“…The observation of the present study that HPGDS transcripts were limited to melanocytes lends further support to a potential role in melanogenesis. Moreover, just as MITF, it was expressed at an early stage of melanocyte maturation which is consistent with the proposition that it may be involved in regulatory feed-back with MITF (Shimanuki et al, 2012; Takeda et al, 2006). Additionally, in human cell lines, it had been shown that prostaglandins positively enhanced tyrosinase activity (Abdel-Malek et al, 1987).…”
Section: Discussionsupporting
confidence: 87%
“…In vitro studies have indicated that L-PGDS mediates cell proliferation via its lipid-carrying function in different cells. In human epidermal melanocytes, normal L-PGDS levels restrict the growth of epidermal melanocytes by transporting all-trans retinoic acid (RA), while its overexpression dysregulates the proliferation of melanoma cells 56 . Additionally, the protein L-PGDS accelerates the migration of glial cells and promotes reactive gliosis by interacting with protein kinase C substrate (MARCKS) 57 .…”
Section: Discussionmentioning
confidence: 99%
“…18 PGD 2 is involved in a wide range of physiologic functions such as sleep induction and regulation, nociception, bronchoconstriction, adipocyte differentiation, nitric oxide release and induction of vasodilation, inflammatory mediator modulation, and inhibition of platelet aggregation. 36 Recent studies also suggest a role for BTP/PGD 2 in maintenance of skin homeostasis, 21 bone remodeling, 24 hair growth inhibition, 22 and immune system modulation in inflammatory conditions of the gastrointestinal tract. 23,37 PGD 2 is metabolized further to other prostanoids such as J series prostaglandins, identified to date only in vitro and therefore with a controversial biological role, and 9a11b-PGF 2 , a mediator of bronchoconstriction.…”
Section: Btp Functionmentioning
confidence: 97%
“…18 In the heart, BTP has been localized to myocardial cells, atrial endocardial cells, synthetic state intimal smooth muscle cells, and fibrous plaques of atherosclerotic stenosed coronary arteries (but not within normal coronary arteries). 18,19 BTP has been described in vascular endothelial cells, 20 skin melanocytes and keratinocytes, 21,22 gastric mucosal epithelial cells, 23 bone osteoblasts, 24 and adipocytes. 25 Within the monkey kidney, BTP localizes to cells of the proximal tubules, loop of Henle, and glomerulus.…”
Section: Btp Tissue Distributionmentioning
confidence: 99%